An Error Analysis of Students' Linguistics Features in Writing Hortatory Exposition Text at MAN 2 Kota Serang - Anisa Paramudita Cahya Kharisma; Ledy Nurlely; Ika Handayani (Journal of Linguistics, Literacy, and Pedagogy, 2022)
The objective of this research was to determine (1) the types of errors that eleventh-grade students at MAN 2 Kota Serang often made while writing hortatory text and (2) the causes of errors in students' hortatory exposition text. The researcher used a qualitative method to analyze and describe the data for this research. As a design, the researcher employed content analysis. The researcher gathered data from students' document, questionnaire, and interview. The students' document was a hortatory exposition text that they wrote, the questionnaire included 10 open-ended questions, and the interview had a few questions regarding how tough it was to write a hortatory exposition text. The instruments were provided to 25 language class students in the eleventh grade of  MAN 2 Kota Serang. According to the result of the research, students made 178 errors. Surface strategy taxonomy was used to classify the error, which was classified into four categories: omission, addition, misformation, and misordering. The most common error produced by the student was misformation, which had 92 or 52% total errors. Besides that, the researcher found that inter-lingual transfer, intra-lingual transfer, and communication strategies were the factors that led students to make errors. The students’ interview, the researcher found that many students still have difficulties in grammar and vocabulary when they write hortatory exposition text.